Insulin-Like Signalling Influences the Coordination of Larval Hemocyte Number with Body Size in Drosophila melanogaster. Issue 7 (1st July 2020) - Bakopoulos, Daniel; Beadle, Lauren Forbes; Esposito, Katherine M; Mirth, Christen K; Warr, Coral G; Johnson, Travis K
Abstract: Blood cells, known as hemocytes in invertebrates, play important and conserved roles in immunity, wound healing and tissue remodelling. The control of hemocyte number is therefore critical to ensure these functions are not compromised, and studies using Drosophila melanogaster are proving useful for understanding how this occurs. Recently, the embryonic patterning gene, torso-like ( tsl ), was identified as being required both for normal hemocyte development and for providing immunity against certain pathogens. Here, we report that Tsl is required specifically during the larval phase of hematopoiesis, and that tsl mutant larvae likely have reduced hemocyte numbers due to a reduced larval growth rate and compromised insulin signaling. Consistent with this, we find that impairing insulin-mediated growth, either by nutrient deprivation or genetically, results in fewer hemocytes. This is likely the result of impaired insulin-like signaling in the hemocytes themselves, since modulation of Insulin-like Receptor (InR) activity specifically in hemocytes causes concomitant changes to their population size in developing larvae. Taken together, our work reveals the strong relationship that exists between body size and hemocyte number, and suggests that insulin-like signaling contributes to, but is not solely responsible for, keeping these tightly aligned during larval development.